(untitled) (Eduscotech, 2024)
This study aims to examine the role of teachers in developing student character and discipline, as well as the influence of discipline on tolerance among students at SLB Al Hidayah Mejayan. The study employed a qualitative descriptive approach, with data collection techniques including in-depth interviews, participatory observation, and document analysis. The research subjects consisted of five teachers and twenty students selected using purposive sampling. The findings indicate that teachers play an essential role in character education by serving as role models through positive reinforcement and the consistent application of discipline. The discipline fostered by teachers contributes to the development of tolerance among students, as more disciplined students tend to demonstrate greater respect for differences and collaborate more effectively with their peers. However, challenges arise when students with special needs experience difficulties in internalizing rules, highlighting the need for more personalized and needs-based approaches to character education. This study contributes to the literature on character education in special education schools and offers recommendations for strengthening teacher training and enhancing collaboration between schools and parents in supporting student character development.